Prancha de identificação para os miriápodos neotropicais (Arthropoda) (Em Portugues e Alemão) - Adis, Joachim (Amazoniana, 1989)
An illustrated key is given in Portuguese and German for the orders of neotropical Myriapoda (Arthropoda).
Bestimmungs -Tafel für neotropische Myriapoda (Arthropoda) (In Portugiesisch und Deutsch)
Keywords: Myriapoda neotropical